(untitled) (Orfeu, 2023)
The study aimed to analyze the quality of the items and dimensions of the Protocol for Screening Musical Skills (PSHM) and aligns its additional instruments. 433 students from Brazilian public and private schools and three judges participated in the study. It was experimental research based on psychometric and psychophysical methods. Descriptive statistical analysis, binomial, exploratory factorial and correlation (item/dimension and between judges) were performed. The results indicated different means between the education mainstreams. Binomial analysis indicated p=0.000 and there is a significant correlation between dimensions and items at level 0.01 in Kendell’s Tau. The PSHM is organized into one factor, in the private mainstream, and two factors in the public one. The correlation between the virtual and printed versions reached a significance level of 0.01 and p<0.05 in the Wilcoxon test. The correlation between the judges’ analysis was significant at the 0.01 and 0.05 levels. It was concluded that PSHM adequately measured musical aptitudes and its additional instruments were aligned.